Fractal signal processing method of acoustic emission monitoring for seismic damage of concrete columns. (21st May 2019) - Huang, Yong; Shao, Changsong; Yan, Xin
In this paper, a new fractal theory-based acoustic emission (AE) signal processing method is proposed. It is found that both the curve lengths and fractal dimensions (FDs) of AE signal are related with damage evolution. The AE tests of pseudo-static experiment of a reinforced concrete column (RCC), a reinforced nano-concrete column and a concrete-filled glass fibre reinforced polymer (GFRP) tube are then performed for validation. For each specimen, several piezoelectric ceramic (PZT) patches and one AE sensor are bonded at different positions of the specimen surface to monitor the AE signals. The results show that the fractal theory-based damage method can assess damage evolution effectively. In addition, the damage can be localised approximately by the diversity of damage assessing index values from various PZT detectors.